The cytoskeleton actin binding protein filamin A impairs both IGF2 mitogenic effects and the efficacy of IGF1R inhibitors in adrenocortical cancer cells. (28th January 2021) - Catalano, R.; Giardino, E.; Treppiedi, D.; Mangili, F.; Morelli, V.; Elli, F.M.; Serban, A.L.; Luconi, M.; Mannelli, M.; Spada, A.; Arosio, M.; Mantovani, G.; et al.
Abstract: Adrenocortical carcinomas (ACCs) overexpress insulin-like growth factor 2 (IGF2), that drives a proliferative autocrine loop by binding to IGF1R and IR, but IGF1R/IR-targeted therapies failed in ACC patients. The cytoskeleton actin-binding protein filamin A (FLNA) impairs IR signalling in melanoma cells. Aims of this study were to test FLNA involvement in regulating IGF1R and IR responsiveness to both IGF2 and inhibitors in ACC. In ACC cells H295R and SW13 and primary cultures (1ACC, 4 adenomas) we found that IGF1R and IR interacted with FLNA, and FLNA silencing increased IGF1R and reduced IR expression, with a downstream effect of increased cell proliferation and ERK phosphorylation. In addition, FLNA knockdown potentiated antiproliferative effects of IGF1R/IR inhibitor Linsitinib and IGF1R inhibitor NVP-ADW742 in H295R. Finally, Western blot showed lower FLNA expression in ACCs (n = 10) than in ACAs (n = 10) and an inverse correlation of FLNA/IGF1R ratio with ERK phosphorylation in ACCs only. In conclusion, we demonstrated that low FLNA levels enhance both IGF2 proliferative effects and IGF1R/IR inhibitors efficacy in ACC cells, suggesting FLNA as a new factor influencing tumor clinical behavior and the response to the therapy with IGF1R/IR-targeted drugs. Highlights: In ACC cell lines FLNA interacts with IGF1R and IR. FLNA silencing increases IGF1R and decreases IR expression. Low levels of FLNA enhance IGF2 proliferative effects in ACC cells. FLNA knockdown potentiates antiproliferative effects of IGF1R inhibitors in H295R. The loss of FLNA might be a biomarker for Linsitinib responsiveness.